REVIEW OF ELECTROMAGNETIC MONITORING STUDIES IN PREDICTING EARTHQUAKES: RECENT RESULTS AND NEW PERSPECTIVES - Piriyev, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In order to make comparisons and find new perspectives in terms of electromagnetic phenomena in earthquake prediction, ULF range was chosen. For comparison, tables consisting of the results of studies from previous years and the last 10 years have been compiled. In order to find new perspectives, the graphs were drawn and comparative analysis was carried out on the basis of these results. It was concluded that the ULF precursors can be found before earthquakes reaching up to 30km in depth, and it can be considered a promising effective range in detecting precursors of earthquakes. In addition, due to the connection between the epicenter distances and the depths of the earthquakes and their magnitudes, attempts to detect the precursors have been made so that the epicenter of the earthquakes is ±100km. The article also provides information about ULF networks and about researchers who had critical opinions on electromagnetic phenomena associated with earthquakes.
Keywords: ULF; earthquake; prediction; electromagnetic; precursor